Fostering Inclusivity: Evaluating the Influence of Leadership Strategies on Cultivating a Diverse and Inclusive School Culture in a Private School in Dubai - AWAWDEH, EMAN (2024)
This research evaluates the influence of leadership strategies on fostering an inclusive school culture in a private school in Dubai. The study employs an explanatory mixed-methods case study approach, which involves a close-ended questionnaire to collect quantitative data from 41 teachers and semi-structured questionnaires for qualitative data from three key school leaders. The results indicate that an inclusive school environment is significantly influenced by effective leadership strategies, including cultural celebration initiatives and continuous professional development. Despite the challenges in implementation, the teachers reported favourable perceptions of the leadership's initiatives to encourage diversity. The research concludes that inclusive leadership practices are essential for addressing the diverse needs of students, and it recommends that additional research investigate these strategies in a variety of educational contexts. These results have significant implications for educational leadership and policy, underscoring the necessity of continuous support and development to maintain an inclusive school culture. Keywords: inclusivity, leadership strategies, school culture